Menedżeryzm w zarządzaniu rozwojem regionalnym - Bandelak-Rosłonkiewicz, Dominika; Kaczmarek, Bogusław (Managerism in Local Development Management, 2005)
The aim of this paper is to point out that local regional development is of a crucial significance for Poland's membership in EU whereas one on the crucial attribute is a high professionalism of management, not the clerical staff. The article analyzes three points of view: - the role of managers in regional development, - crucial organizational issues in this respect, and - coordinative aspects of regional development management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 31-38